UJI AKTIVITAS ANTIOKSIDAN EKSTRAK AKAR BAKAU HITAM (Rhizophora mucronata (Lamk.)) DENGAN METODE DPPH (2,2-diphenyl-1-picrylhydrazyl) - Sulistiorini, Indah; Mahmiah, Mahmiah; Sudjarwo, Giftania Wardan (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2023)
Indonesia is a country that has a variety of marine ecosystems that have a lot of potential, one of which is mangroves. Rhizophora mucronata is a species in the mangrove ecosystem in Indonesia. Rhizophora mucronata or black mangroves are plants that contain various kinds of compounds. Antioxidants play an important role in the prevention of degenerative diseases. This research is motivated by the presence of carcinogenic dangers caused by consuming synthetic antioxidants at high doses synthetic antioxidants can function as prooxidants which can increase oxidative stress and damage body cells, so it wants to explore the natural antioxidant potential of Rhizophora mucronata. Rhizophora mucronata root was chosen in this study because no one has examined the potential of this plant that grows in the Pamurbaya area, Surabaya - East Java as an antioxidant. This study aims to determine the content of secondary metabolites and antioxidant activity of the root extract of Rhizophora mucronata. In this study, the antioxidant activity test used the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The results showed that the antioxidant activity of the methanol extract of Rhizophora mucronata root had very weak antioxidant activity with an IC50 value of 2604.56 ppm. The antioxidant potential of the methanol extract of Rhizophora mucronata root has an IC value of 50 with a very weak antioxidant intensity